Distribution and solar wind control of compressional solar wind‐magnetic anomaly interactions observed at the Moon by ARTEMIS. Issue 6 (21st June 2017) - Halekas, J. S.; Poppe, A. R.; Lue, C.; Farrell, W. M.; McFadden, J. P.
Abstract: A statistical investigation of 5 years of observations from the two‐probe Acceleration, Reconnection, Turbulence, and Electrodynamics of Moon's Interaction with the Sun (ARTEMIS) mission reveals that strong compressional interactions occur infrequently at high altitudes near the ecliptic but can form in a wide range of solar wind conditions and can occur up to two lunar radii downstream from the lunar limb. The compressional events, some of which may represent small‐scale collisionless shocks ("limb shocks"), occur in both steady and variable interplanetary magnetic field (IMF) conditions, with those forming in steady IMF well organized by the location of lunar remanent crustal magnetization. The events observed by ARTEMIS have similarities to ion foreshock phenomena, and those observed in variable IMF conditions may result from either local lunar interactions or distant terrestrial foreshock interactions. Observed velocity deflections associated with compressional events are always outward from the lunar wake, regardless of location and solar wind conditions. However, events for which the observed velocity deflection is parallel to the upstream motional electric field form in distinctly different solar wind conditions and locations than events with antiparallel deflections. Consideration of the momentum transfer between incoming and reflected solar wind populations helps explain the observed characteristics of the different groups of events. Plain Language Summary: We survey the environment around the Moon to determine when and where strong amplifications in the charged particle density and magnetic field strength occur. These structures may be some of the smallest shock waves in the solar system, and learning about their formation informs us about the interaction of charged particles with small‐scale magnetic fields throughout the solar system and beyond. We find that these compressions occur in an extended region downstream from the lunar dawn and dusk regions and that they can form under a wide variety of solar wind conditions. However, we find that two distinctly different types of interactions occur for different magnetic field geometries and solar wind conditions. The two types of events appear to differ because of the different trajectories followed by solar wind protons that reflect from localized lunar magnetic fields and the resulting differences in how the incoming solar wind from upstream interacts with these reflected particles. Key Points: Compressional structures form at the Moon with deflections both parallel and antiparallel to upstream electric fields, but always outward Events with parallel and antiparallel velocity deflections have distinct characteristics and form under different solar wind conditions Momentum transfer between the solar wind and protons reflected from magnetic anomalies plays a key role in the formation of compressions